GAMBARAN POPULASI DAN BIONOMI Anopheles spp DI PULAU DOMPAK KOTA TANJUNGPINANG PROVINSI KEPULAUAN RIAU TAHUN 2016 - Mohd Abd Rahman; Martini Martini; Retno Hestiningsih (Jurnal Kesehatan Masyarakat (Undip), 2016)
Malaria remains a health problem, especially in the city of Tanjungpinang. Dompak Island is one of a malaria endemic area in the city of Tanjungpinang. Dompak island environment conducive to the breeding of Anopheles spp. This study aims to determine species Anopheles spp, bionomi Anopheles spp, nature and density of larval breeding places as well. is a descriptive study with cross sectional approach were held from November 2015 through to May 2016 on the island of Dompak Tanjungpinang. Samples were taken throughout the breeding sites of Anopheles spp in this island and four villages there to survey the vector see many mosquitoes or Man Haour Density (MHD) using Night Landing Collection (NLC) and the Night Resting Collection (NRC) with man bait Insider (MBI) and man bait outsiders (MBO). The results of this study get 12 Anopheles mosquito breeding sites with varying density values. A total of 4 species of Anopheles were found, namely: An maculatus (MHD 3.51), An. sundaicus (MHD 1.46), An. subpictus (MHD 1.29) and An. sinensis (MHD 1.66). Suggestions for the City Health Office, the survey should continue to entomology face Dompak implemented in the island in order to prevent outbreaks of malaria although currently not encountered cases of malaria. The increase in human resources and equipment to support the activities of entomology survey.